The Bodily Experiences of Music Teachers - Girdzijauskienė, Rūta (Central European Journal of Educational Research, 2021)
This paper deals with the specifics of a music teacher's work in kindergarten and presents an empirical study, based on the approach of hermeneutic phenomenology. In the research outcomes, the experiences of the music teacher's work in kindergarten are presented through their stories about memorable moments of their professional activity. Initially, in accordance with the theory of Max van Manen, the research data were viewed through the prism of five dimensions (lived time, lived space, lived self-others, lived things, and lived body), typical of all phenomena. The paper discusses one of them, i.e. the teachers' experience from the perspective of the lived body. The stories demonstrate how through the looks, facial mimicry, and body language, moments of the teacher's everyday routine are revealed that would otherwise be overlooked or considered irrelevant.